India after Gandhi : the history of the world's largest democracy - Guha, Ramachandra (Picador, 2007)
"Born against a background of privation and civil war, divided along lines of caste, class, language and religion, independent India emerged, somehow, as a united and democratic country. This book tells the full story - the pain and the struggle, the humiliations and the glories - of the world's largest and least likely democracy." "Ramachandra Guha writes of the myriad protests and conflicts that have peppered the history of free India. But he writes also of the factors and processes that have kept the country together (and kept it democratic), defying numerous prophets of doom who believed that its poverty and heterogeneity would force India to break up or come under autocratic rule. Once the Western world looked upon India with a mixture of pity and contempt; now it looks upon India with fear and admiration."--BOOK JACKET.